ASEAN and foreign economic policy of the Russian Federation ("Journal "U". Economy. Management. Finance.", 2025)
The article considers ASEAN and foreign economic policy of the Russian Federation. “Turn to the East”, taking into account the transition from Russia's traditional Western partners to the countries of the Asian region, has a high relevance at present. The authors revealed the peculiarities of interaction between Russia and ASEAN countries, the impact of the formation of new institutions and business environment in SEA countries on Russian-Asian economic cooperation. The main approaches of ASEAN to the development of cooperation outside the group, the prospects of partnership between Russia and ASEAN are revealed.
Keywords: ASEAN; foreign economic policy; Southeast Asia; turn to the East; sustainable development; Russia's partnership